Sensitivity of Campylobacter jejuni Virulence genes flaA,mapA and hipO by Polymerase chain reaction - Marimuthu, Dhanalakshmi; Sekar, Muthu; L, Gunasaleen; Vivekanandan, Bhanurekha; Singaram, Balakrishnan; Raj, Gopal Dhinakar (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Campylobacter jejuni is more frequently associated with zoonotic bacterial cause of foodborne gastroenteritis in humans. Effective diagnosis of C. jejuni infection in various matrix like foods of animal origin, environment and human is crucial to maintain public health. Since molecular diagnosis of C. jejuni carries several advantages over conventional microbial culture techniques, in this study, the limit of detection for the selected virulence genes of C. jejuni (flaA,mapA and hipO) were evaluated to know the suitability of them to be used as molecular diagnostic targets for early detection of C. jejuni by in- house designed primers by conventional PCR. Analytical sensitivity of these genes were assessed in terms of Colony Forming Units (103 CFU/ ml, 102 CFU/ ml, 101 CFU/ ml, 100 CFU/ ml) and DNA concentration (100 ng,10 ng, 1 ng, 100 pg, 10 pg and 1 pg ) of C jejuni cultures. Results revealed that the primers targeting flaA have superior limit of detection as 10CFU and 1pg of C. jejuni DNA. Whereas mapA and hipO have 10 CFU; 10 pg DNA and 100 CFU ;10 ng DNA detection limit respectively. Gene mapA had comparable detection limits in terms of CFU with flaA but found to be less sensitive with respect to DNA concentration but hipO has 102 fold lesser limit of detection.